CLINICAL AND PROGNOSTIC FEATURES OF PATIENTS WITH UNSTABLE ANGINA AND CHRONIC HEART FAILURE WITH PRESERVED EJECTION FRACTION: RESULTS OF CONSERVATIVE TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study evaluated the clinical and prognostic features of patients with unstable angina and chronic heart failure with preserved left ventricular ejection fraction (HFpEF) under conservative treatment, as well as their association with other factors. The study was conducted at the Samarkand Regional Branch of the Republican Specialized Scientific and Practical Medical Center of Cardiology (SRB RSSPMC). The study included 80 patients aged 50 to 70 years (40 men and 40 women) with coronary artery disease complicated by HFpEF at stages I–IIA, functional class I–III (FC).